Spatial analysis of land subsidence potential due to lowland conversion (case study at Tanjung Api-Api). Issue 1 (September 2020) - Andriani,; Ibrahim, E; Putranto, D D A; Affandy, A K; Putra, H G
Abstract: The conversion of lowland area into special economic zones at Tanjung Api-Api will trigger environmental degradations, one of which is land subsidence. Land subsidence potential is caused by several natural environmental factors, which are soil type, soft soil thickness, topography, geological conditions, and rainfall, and non-natural factors, which are caused by land use or land cover, groundwater extraction, building density and others. Multicriteria analysis was conducted to obtain the weight of each factor, then the factor was overlayed to determine the level of land subsidence based on land use or land cover. Spatial analysis has been done to many factors causing land subsidence. The results showed that industrial estates and housing areas have a high potential for land subsidence. Mitigation efforts must be carried out to reduce severe land subsidence at the built-up area.